Strategi dan Media Pembelajaran Sejarah dalam Menghadapi Tantangan Abad ke-21 - Muh. Akbar; Bahri; Andi Dewi Riang Tati (CV. Ulil Albab Corp, 2026)
21st century history education demands the development of the 4C skills (Critical thinking, Creativity, Communication, and Collaboration) however, classroom practice remains dominated by conventional methods with minimal use of technology. This study aims to reconstruct instructional strategies, the transformation of digital media visualization, and an integration framework for 21st-century history education. Employing a qualitative approach, the study utilizes a literature review method based on data from reputable scholarly sources. The findings indicate that Problem-Based Learning and Cooperative Learning effectively transform students into active, critical analysts. Visual transformation through immersive technologies such as Virtual Reality and Augmented Reality enables abstract concepts to be presented in concrete terms. Furthermore, the integration of 21st-century history education is achieved through the intersection of active instructional strategies acting as software and digital media acting as visual hardware this combination systematically fosters the 4C skills and shapes students' multicultural character. The success of history education hinges on a holistically integrated framework designed to equip the younger generation to counter disinformation in the digital era.